2011
DOI: 10.1039/c0jm03485a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of lamellar-structured silica thin films with high thermal stability greater than 450 °C

Abstract: We synthesized lamellar-structured silica thin films with various repeating distances in the range 5.9-8.8 nm. The synthesis was achieved through the self-assembly of a silica precursor (tetraethoxyorthosilicate) and a non-ionic triblock copolymer F-127 ((EO) 106 (PO) 70 (EO) 106 , EO ¼ ethylene oxide, PO ¼ propylene oxide), followed by calcination. The lamellar structure was unambiguously confirmed by small angle X-ray diffraction, grazing incidence small angle X-ray scattering, transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…These values were found to monotonically increase up to around 18.2 and 1.14 GPa after annealing at 300 °C; these values finally reached 33.7 and 2.63 GPa, respectively, after the annealing at 500 °C. The resulting mechanical robustness is close to that found in the relevant study related to pyrolytic converted silica (previously reported Young's modulus and hardness were 31.62 and 2.31 GPa, respectively) 50 and far above that of traditional organic materials (in general, organic materials have Young's modulus values below 10 GPa and hardness values below 0.2 GPa). 51À53 These results clearly indicate that the silica pattern maintains the intrinsic mechanical robustness of silica.…”
Section: Articlesupporting
confidence: 86%
“…These values were found to monotonically increase up to around 18.2 and 1.14 GPa after annealing at 300 °C; these values finally reached 33.7 and 2.63 GPa, respectively, after the annealing at 500 °C. The resulting mechanical robustness is close to that found in the relevant study related to pyrolytic converted silica (previously reported Young's modulus and hardness were 31.62 and 2.31 GPa, respectively) 50 and far above that of traditional organic materials (in general, organic materials have Young's modulus values below 10 GPa and hardness values below 0.2 GPa). 51À53 These results clearly indicate that the silica pattern maintains the intrinsic mechanical robustness of silica.…”
Section: Articlesupporting
confidence: 86%
“…S7). Given that lamellae-like orderings cannot be generally sustained after the removal of the template without layer stabilization, 38,39 preservation of the lamellae-like layering found here can be attributed to the presence of the interdigitated state of the framework (i.e., whereby resisting towards the structural collapse) and associated stabilization of the layering modes. Indeed, a careful observation of the higher-magnification micrograph (of the pointed area in Fig.…”
Section: Resultsmentioning
confidence: 75%
“…[ 40,41 ] Subsequent particles impact, fragment as well, and consolidate the underlying particles to a dense ceramic film. [ 42 ] This mechanism is also referred to as “hammering effect.” [ 43,44 ] As a direct observation of the impacting and fracturing particles is very difficult, molecular dynamics (MD) simulations could play a key role to investigate the deposition mechanism. [ 45 ] However, results of this study can only be taken into account partially in our study, since the impact of nanoparticles was simulated, and nanoparticles usually get deflected by the stagnation point flow in the real application and cannot reach the substrate at all.…”
Section: Introductionmentioning
confidence: 99%